Submitral Left Ventricular Aneurysms: Correction through a Transmitral Approach - Chirag Doshi; Sumit Modi; Aakash Joshi; Ibrahim Mohammed; Mausam Garachh; Opjinder Deepak (Journal of Cardio-Thoracic Medicine)
Introduction: Submitral aneurysms (SMA) are a rare heart condition that is more common among young Africans. The etiology is primarily congenital, but when SMA is found in patients of other races, other etiologies must be sought, especially ischemic. The other suggested aetiologies are infection and inflammation. Patients with submitral aneurysms can present with a variety of clinical manifestations.Case presentation: We present the case of a 57-year-old male patient who was asymptomatic and admitted for evaluation. Transthoracic echocardiography revealed a submitral aneurysm.Clinical discussion: Submitral left ventricular aneurysm is a rare cardiac pathology with various of causes including inflammation, infection, traumatic illness, or, in rare instances, ischemic heart disease. It can result from a congenital defect in the posterior portion of the mitral annulus, which is more prevalent in the African population. Clinical manifestations can be severe, such as ventricular tachycardia, cardiogenic shock or an embolic phenomenon. However, asymptomatic cases are possible but uncommon.Conclusion: Our case highlights that SMA can be either the cause or result of coronary ischemia, emphasizing the importance of vigilance in patients with atypical clinical presentations.